Study on the Comfort of 3 Local Hijab Sport Brand on Muslim Woman during Physical Activities. Issue 1 (August 2021) - Baharudin, A; Hafidz, A H A; Roslan, N M; Zahir, I N; Norjeferi, N A; Musa, A; Ahmad, M R
Abstract: This study goals are to identify the most comfortable sport hijab from 3 local brands. The selection of the sport hijab from the brand are identify through a preliminary survey distributed to 90 students from Faculty of Sport Science UiTM Negeri Sembilan. From the survey, types of sport hijab and the length of sport hijab are identified. The purchased sport hijab is then gone through the fabric identification and testing included weighing, burning test and water impact penetration test. The fabric for the sport hijab labelled as Sample A is Nylon, Sample B as Polyester and Sample C as Acrylic. Among this, it is found that Sample B gives the best comfort according to all 3 selected respondent who wear the sport hijab in the physical test activities. The physical test activities are done by the 3 participants running on a treadmill for 20 minutes at 7.5km/h with warming up and warming down at 2.5km/h for 2 minutes. The results obtained from the comfort evaluation were then analyzed using Analysis of Variance (ANOVA).